Signs of Intracranial Hypertension, Hypermobility, and Craniocervical Obstructions in Patients With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Bragée, Björn; Michos, Anastasios; Drum, Brandon; Fahlgren, Mikael; Szulkin, Robert; Bertilson, Bo C. (Frontiers in Neurology, 2020)
The pathophysiology of myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is unknown. In this study we test the hypothesis that hypermobility, signs of intracranial hypertension (IH) and craniocervical obstructions may be overrepresented in patients with ME/CFS and thereby explain many of the symptoms. Our study is a retrospective cross-sectional study, performed at a specialist clinic for referred patients with severe ME/CFS, as defined by the Canada Consensus Criteria. The first 272 patients with ME/CFS were invited to participate, and 229 who provided prompt informed consent were included. Hypermobility was assessed using the Beighton Score. IH was assessed indirectly by the quotient of the of optic nerve sheet diameter (ONSD)/eyeball transverse diameter on both sides as measured on magnetic resonance imaging (MRI) of the brain. We also included assessment of cerebellar tonsil position in relation to the McRae line indicating foramen magnum. Craniocervical obstructions were assessed on MRI of the cervical spine. Allodynia was assessed by quantitative sensory testing (QST) for pain in the 18 areas indicative of fibromyalgia syndrome (FMS). A total of 190 women, mean age 45 years, and 39 males, mean age 44 years, were included. Hypermobility was identified in 115 (50%) participants. MRI of the brain was performed on 205 participants of whom 112 (55%) had an increased ONSD, 171 (83%) had signs of possible IH including 65 (32%) who had values indicating more severe states of IH. Cerebellar tonsils protruding under the McRae line into the foramen magnum was identified in 115 (56%) of the participants. MRI of the cervical spine was performed on 125 participants of whom 100 (80%) had craniocervical obstructions. Pain at harmless pressure, allodynia, was found in 96% of the participants, and FMS was present in 173 participants, or 76%. Compared to a general population we found a large overrepresentation of hypermobility, signs of IH and craniocervical obstructions. Our hypothesis was strengthened and future studies on possible relation between ME/CFS symptoms and hypermobility, IH and craniocervical obstructions in a portion of patients with ME/CFS. If our findings will be confirmed, new diagnostic and therapeutic approaches to this widespread neurological syndrome should be considered.